Self-Efficacy Perceptions of Turkish Foreign Language Students of ?stanbul Geli?im University - GÖK, Şahin (International Journal of Language and Literary Studies, 2025)
Abstract Background: Self-efficacy, a core construct of Bandura’s (1986) social cognitive theory, significantly influences motivation, persistence, and resilience in learning. This study examines the self-efficacy perceptions of English Language and Literature students at Istanbul and Gelisim University in the context of foreign language learning. Method: A qualitative case study design was employed. Data were collected through students’ written responses to three open-ended questions and analyzed thematically. Findings: Students defined self-efficacy as confidence in their abilities, persistence through challenges, and a learnable skill shaped by education and experience. They emphasized its role in sustaining motivation, overcoming fear of failure, supporting self-study, and guiding academic choices. Broader insights included career adaptability, daily responsibilities, and emotional resilience. Conclusion: The study confirms the strong link between self-efficacy and language achievement. Educational programs should integrate strategies to strengthen self-efficacy, thereby promoting academic success and lifelong learning.